Conversion of High Speed Landing Craft Boat for Passenger into High Speed Landing Craft Boat for Ambulance - Prayetno, Eko; Verandi, Alde Vio; Uzri H.A, Islam; Putra, Risandi Dwirama; Nusyirwan, Deny (International Journal of Marine Engineering Innovation and Research, 2024)
The Riau Archipelago is one of the provinces that geographically consist of 1700 islands surrounded by sea, both small and large, with a percentage of 98% sea and 2% land. So, to support the minimal health facilities on the Riau Archipelago, an Ambulance Boat is needed to mobilize patients to hospitals with better facilities. In this study, it aims to modify the design of the High Speed Landing Craft Boat Passenger to become an Ambulance Boat with a length of 12 m, a width of 3 m, a height of 1.2 m, and a draft of 0.6 m. Then perform technical calculations including hull shape coefficient analysis, stability, seakeeping, resistance, speed, ship power, and Motion Sickness Incidence (MSI) analysis. From MSI analysis with ISO 2631 parameters, the wave heading is divided into 5 sections: 00 (Following Seas), 450 (Stern Quartering Seas), 900 (Beam Seas), 1350 (Bow Quartering Seas), and 1800 (Head Seas). The value MSI is obtained after carrying out a comprehensive analysis, the results are depicted in the MSI chart for sea state 1 calm (0-0.1 m) and sea state 2 smooth (0.1-0.5 m) conditions with the following wave directions, waves coming from the side (beam seas), and waves coming from the front (head seas).